AN ERROR ANALYSIS OF USING SIMPLE PRESENT TENSE IN DESCRIPTIVE TEXT WRITTEN BY THE EIGHTH GRADE STUDENTS OF SMP BINA SATRIA MEDAN - Nurlaili Nurlaili; Juliana Juliana (Universitas Potensi Utama, 2021)
This research is aimed to find out types of error analysis of using simple present tense in descriptive text written by the eighth grade students of SMP Bina Satria Medan. This research used the qualitative research design. The sample of this research was the eighth grade students of SMP Bina Satria Medan which consisted of 20 students. The result of the data analysis showed that there were the types of errors made by the students on writing descriptive text based on surface strategy taxonomy which are classified into omission, addition, misformation, and misordering. The types of errors made by the students on writing descriptive text were 25% in errors of omission, 22,4% in errors of Addition, 49,2% in errors of Misformation, 3,4 % in errors of Ordering. From this data, it can be said that the misformation error was the highest number of errors made by the students in 49,2%.There were some causes of errors made by students in misformation. Firstly, the students felt confused with tense formula, they still could not distinguish regular and irregular verbs, which are present tense and past tense. Secondly, the students made mistakes in arranging word or confused to select the word sequence in sentence which important to formation writing that meanwhile to arrange the word and group of words in English and Indonesia are different. Thirdly, The students made errors because they didn’t know grammar rule, they were lazy to learn about tense, they couldn’t interpret sentences or paragraph directly and many other reasons. Therefore, it can be stated that source of the errors made by students influenced by interlingual and intralingual transfer(Corder, 2000). Interlingual transfer is errors that are influenced by the interference of users’ mother tongue. The users still apply Indonesian pattern into English when they translate the sentences. Then Intralingual transfer occurs when students get difficulty learn the second language. Three causes of errors in intralingual transfer, namely; errors caused by over-generalization, errors caused by ignorance of rule restriction, and errors caused by incomplete application of rules.